Mathematical modeling of radiolysis process of water under the impact of low-energy electrons - Jafarov, Y.D. (Вопросы атомной науки и техники, 2011)
The radiolysis process of water (liquid phase) under the impact of low - energy electrons (E = 1, 2.5, 5, 10 keV ) was mathematically modeled using Monte-Carlo, single collision and pacing methods on the base of Mathcad program. The radiation-chemical yields of the physical (single ionized molecular orbitals - H₂O⁺j (1a₁, 2a₁, 1b₁, 3a₁, 1b₁), e⁻sub electron - lost its energy up to a primary electron - excited energy and electron-excited states: H₂O* (A¹B₁, B¹A₁, Rydberg state, diffusion band, dissociative excitation and plasmon-H₂O**) and physicochemical (OH, e⁻aq, H, H₃O+, H₂, H₂O₂, HO₂, O₂, OH⁻, O⁻₂, HO⁻₂ ) phase products of the non-elastic collision of electrons and water molecules were determined. Проведено математичне моделювання радіолізу води (фаза рідини) під дією електронів з малою енергією (E = 1, 2.5, 5, 10 кеВ) за допомогою програми Mathcad з використанням Монте-Карло, однократних зіткнень та шагового методів. На основі цієї моделі обраховані радіаційно-хімічні виходи слідуючих продуктів непружних зіткнень електронів з молекулами води: фізичні (одноіонізовані молекулярні орбіталі - H₂O⁺j (1a₁, 2a₁, 1b₁, 3a₁, 1b₁) електрони з енергією, пониженою до рівня з першим електронно-збудженим станом - e⁻sub, і електронно-збуджені стани - H₂O* (A¹B₁, B¹A₁, рідберговскі стани, полоса дифузії, дисоціативне збудження і плазмон - H₂O**) і фізико-хімічна стадія (OH, e⁻aq, H, H₃O+, H₂, H₂O₂, HO₂, O₂, OH⁻, O⁻₂, HO⁻₂). Проведено математическое моделирование радиолиза воды (жидкая фаза) под действием электронов с малой энергией (E=1, 2.5, 5, 10 кэВ) при помощи программы Mathcad с использованием Монте-Карло, однократных столкновений и шагового методов. На основе этой модели вычислены радиационно-химические выходы следующих продуктов неупругих столкновений электронов с молекулами воды: физические (одноионизированные молекулярные орбитали -H₂O⁺j (1a₁, 2a₁, 1b₁, 3a₁, 1b₁), электроны с энергией, снизившейся до уровня с первым электронно-возбужденным состоянием - e-sub, и электронно-возбужденные состояния - H₂O*(A¹B₁, B¹A₁, ридберговские состояния, полоса диффузии, диссоциативное возбуждение и плазмон - H₂O**) и физико-химическая стадия (OH, e⁻aq, H, H₃O+, H₂, H₂O₂, HO₂, O₂, OH⁻, O⁻₂, HO⁻₂).